Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Minat Berkunjung Wisatawan di Karang Setra Waterland - Asti Karini, Rieke Sri Rizki; Azziz, Mochamad Abdul (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2024)
Quality of Service and Facilities is the most important thing in every tourist destination, so if these two things are done well, it will automatically affect the interest in visiting. Thus, this study aims to determine how the influence of the quality of services and facilities on the interest in visiting Karang Setra Waterland. The method used is a verifiative descriptive quantitative method. The types used in this study are primary data and secondary data. The population in this study was taken from the average tourist visits in 2019-2023 of 4,700 and the sample used amounted to 100 respondents, the results of using the Slovin formula. The sampling technique is carried out by survey or questionnaire. Data collection was done by observation, questionnaires, interviews, and documentation. The questionnaire model in this study used the Likert Scale. The verifiative analysis used in this study is instrument test (validity test and reliability test), normality test, multiple linear regression analysis, determination analysis, and partial and simultaneous hypothesis test. The results of this study show that each statement item is said to be valid and reliable. The influence of the independent variable on the dependent variable in this study was 52.70%. The results of partial and simultaneous hypothesis tests show that the Quality of Service ( ) and Facilities ( ) has a positive and significant effect partially and simultaneously on Visiting Interest (Y) in Karang Setra Waterland.